Nitrogen sequestration during sewage sludge composting and vermicomposting - Zigmontienė, Aušra; Šerevičienė, Vaida (Journal of Environmental Engineering and Landscape Management, 2023)
Composting is the oldest and most natural form of organic material recycling. Technological parameters are very important because when the process is unbalanced, other gases are produced, some of which have objectionable odours (NH3). Sewage sludge is a valuable material that has accumulated large amounts of nitrogen and phosphorus, which can contribute to improving soil quality. Optimal composting and vermicomposting conditions (C/N ratio, pH, and moisture) can reduce the emissions of gaseous pollutants in the environment. Experimental studies have shown that the volume of ammonia emitted into the environment during vermicomposting of sewage sludge is significantly lower (3 mg/m3 concentration was reached on the 28th day) than that resulting from traditional composting (3 mg/m3 concentration was reached on the 56th day). Vermicomposting of sewage sludge preserves higher amounts of total nitrogen (12.52 mg/kg) compared to traditional composting (10.35 mg/kg).